Facts & fiction : arte e narrazione - La Generazione delle immagini IV - Abramović, Marina; Amadasi, Giovanna; Calle, Sophie; Douglas, Stan; Durham, Jimmie; Fusco, Coco; Kentridge, William; Lissoni, Andrea; Rist, Pipilotti; Scalpelli, Sergio; Wallis, Brian (Milano : Comune di Milano, 1998)
Durham, Jimmie ; Douglas, Stan ; Kentridge, William ; Abramovic, Marina ; Rist, Pipilotti ; Fusco, Coco ; Calle, Sophie ; Lockhart, Sharon ; Wegman, William ; Salle, David ; Clark, Larry ; Horn, Rebecca ; Grimonprez, Johan ; Huyghe, Pierre ; Leccia, Ange ; Gonzalez-Foerster, Dominique ; Webb, Boyd ; Ahtila, Eija-Liisa ; Hirst, Damien ; Barney, Matthew ; Donegan, Cheryl ; Shephard, Greg ; Fischli, Peter ; Weiss, David ; Buvoli, Luca ; Schnabel, Julian ; Boltanski, Christian ; Jarman, Derek ; Studio Azzuro
Italiaans & Engels
Facts & fiction : arte e narrazione, Comune di Milano, 05.11.1997 - 30.06.1998
boek